PELAKSANAAN FIDUSIA SEBAGAI JAMINAN KREDIT DITINJAU DARI SEGI PENGAMANANNYA DALAM PRAKTEK DI PT. BATAVIA PROSPERINDO FINANCE SAMARINDA - Al Mutakkim (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACTThe right to acquire the remaining insurance payments occur in the event of loss of a motor vehicle as collateral objects. In this case PT. BATAVIA Prosperindo Finance has the right to file an insurance claim. If the net proceeds of the insurance compensation payment exceed the surplus remaining debt into consumer rights but when less then the drawbacks is the responsibility of the consumer of the consumer to pay to PT. BATAVIA Prosperindo Finance. With the loss of objects and guarantees the completion of insurance claims and the calculation of the entire debt financing terlunasinya consumers by fiduciary guarantee an end in itself.       This is a proof of fiduciary assurance in terms of safety. Consumer debtor who has transferred or guarantee objects to a 3rd party without the knowledge and permission of PT. BATAVIA Prosperindo Finance, but during the installment payment lancer PT. BATAVIA Prosperindo Finance does not pull the vehicle but by taking the family way is by calling debtor or consumer and 3rd party to perform credit transfer or shift gears. As for the issues related to bad credit problems can be solved by means of deliberation and kinship and the debtor or consumer through its field employees, but in urgent situations PT. BATAVIA Prosperindo Finance will involve law enforcement authorities, in this case the police local area to be a mediator or arbitrator settlement which is based on a civil agreement that consumer financing agreement or accounts payable. Keywords: Fiduciary Implementation, Credit Guarantee, PT. Batavia Prosperindo Finance.